Impaired ergosterol biosynthesis mediated fungicidal activity of Co(II) complex with ligand derived from cinnamaldehyde. (5th March 2016) - Shreaz, Sheikh; Shiekh, Rayees A.; Raja, Vaseem; Wani, Waseem A.; Behbehani, Jawad M.
Abstract: In this study, we have used aldehyde function of cinnamaldehyde to synthesize N, N′-Bis (cinnamaldehyde) ethylenediimine [C20 H20 N2 ] and Co(II) complex of the type [Co(C40 H40 N4 )Cl2 ]. The structures of the synthesized compounds were determined on the basis of physiochemical analysis and spectroscopic data ( 1 H NMR, FTIR, UV–visible and mass spectra) along with molar conductivity measurements. Anticandidal activity of cinnamaldehyde its ligand [L] and Co(II) complex was investigated by determining MIC80, time-kill kinetics, disc diffusion assay and ergosterol extraction and estimation assay. Ligand [L] and Co(II) complex are found to be 4.55 and 21.0 folds more efficient than cinnamaldehyde in a liquid medium. MIC80 of Co(II) complex correlated well with ergosterol inhibition suggesting ergosterol biosynthesis to be the primary site of action. In comparison to fluconazole, the test compounds showed limited toxicity against H9c2 rat cardiac myoblasts. In confocal microscopy propidium iodide (PI) penetrates the yeast cells when treated with MIC of metal complex, indicating a disruption of cell membrane that results in imbibition of dye. TEM analysis of metal complex treated cells exhibited notable alterations or damage to the cell membrane and the cell wall. The structural disorganization within the cell cytoplasm was noted. It was concluded that fungicidal activity of Co(II) complex originated from loss of membrane integrity and a decrease in ergosterol content is only one consequence of this. Graphical abstract: Highlights: In liquid medium ligand [L] and Co(II) complex were 4.55 and 21.0 fold more effective than cinnamaldehyde. MIC80 of Co(II) complex correlated well with ergosterol inhibition. Microscopic analysis of treated cells indicated disruptions of cell wall and membrane. Fungicidal activity of Co(II) complex originates from loss of membrane integrity and decrease in ergosterol content. In comparison to fluconazole Co(II) complex exhibited limited toxicity.